The novel copper(I) π, σ-complexes with 1-(aryl)-5-(allylthio)-1H-tetrazoles: Synthesis, structure characterization, DFT-calculation and third-order nonlinear optics. Issue 5 (3rd April 2019) - Slyvka, Yurii; Goreshnik, Evgeny; Veryasov, Gleb; Morozov, Dmitry; Fedorchuk, Andrii A.; Pokhodylo, Nazariy; Kityk, Iwan; Mys'kiv, Marian
Abstract: The present work is directed toward preparation, structure and optical property characterization of tetrazole-containing Cu(I) compounds. By means of the alternating-current electrochemical technique copper(I) π, σ-compounds with 1-(4-methylphenyl)- ( Matht ), 1-(3-chloro-4-methylphenyl)- ( Chmatht ) and 1-[2-(trifluoromethyl)phenyl]- ( Tfmatht ) 5-(allylthio)-1 H -tetrazoles were obtained in a single crystal form and structurally characterized by X-ray diffraction and Raman spectroscopy. Matht and Chmatht ligands, being attached to the Cu(I) through S-allylic C = C-bond and two tetrazole N-atoms, form stable centrosymmetric dimers [Cu2 ( Matht )2 (H2 O)2 ](BF4 )2 and [Cu2 ( Chmatht )2 (СlO4 )2 ]. The presence of an electron acceptor trifluoromethyl group promotes formation of the monomeric [Cu( Tfmatht )2 ]BF4 and [Cu( Tfmatht )(NH2 SO3 )(MeOH)] compounds. The compounds were investigated by means of Raman spectroscopy, third-order nonlinear optics and DFT calculations. Abstract :